Board gender diversity, governance and Egyptian listed firms' performance. Issue 2 (12th August 2021) - Ramadan, Maha Mohamed; Hassan, Mostafa Kamal
Abstract : Purpose: The study aimed to examine the effect of corporate governance mechanisms on the performance of Egyptian firms listed in the Egyptian Stock Exchange (EGX) between 2014 and 2016. Design/methodology/approach: We relied on agency theory and resource dependence theory to generate testable hypotheses and capture the empirical findings. We regressed various performance measures (Return on Assets; Asset Utilization Ratio, Tobin's Q ) regarding governance mechanisms (institutional ownership, managerial ownership, board size, board frequent meetings, the presence of non-executive directors and female directors) while controlling for firm size, leverage, years of listing and market share. The study uses ordinary least square (OLS) and two stages least square (2SLS) regression analysis to address the possible endogenous impact of the firms' ownership structure. Findings: Board gender diversity, the managerial ownership and frequent board meetings positively influence the Egyptian firms' efficiency measured by assets utilization, while the institutional ownership and board size have negative effects. When using Tobin's Q, the managerial ownership shows a negative effect while institutional ownership and board size present positive effects. When using 2SLS regression, findings remained stable whereas non-executive directors showed a significant negative association with assets utilization. Practical implications: Policy makers are recommended to draft policies related to limiting the number of board members, diluting the government's indirect ownership of firms, empowering women in boardrooms and developing the skills needed for non-executive directors. Originality/value: To the best of our knowledge, our study is one of very few that address firms' performance after a period of political instability accompanied by a greater role for females in the boardrooms of Egypt.